Paraboloid-Ellipsoid Programming Problem - Ismail Bin Mohd (International Conference on Engineering and Technology Development (ICETD), 2012)
In this paper, we discuss the state-of-the-artÂ models in estimating, evaluating, and selecting among nonlinearÂ mathematical models for obtaining the optimalÂ solution of the optimization problems which involve theÂ nonlinear functions in their constraints. We reviewÂ theoretical and empirical issues including NewtonâsÂ method, linear programming, quadratic ogramming,Â quadratically constrained programming, parabola, ellipseÂ and the relation between parabola and ellipse. Finally, weÂ outline our method called paraboloid-ellipsoidÂ programming which is useful for solving economicÂ forecasting and financial time-series with non-linearÂ models.